Implementasi Sistem Informasi Manajemen Nikah Online (Simkah) dalam Administrasi Pernikahan di Kua Kecamatan Bajeng Kabupaten Gowa - Muh. Jamal Jamil (Syntax Corporation Indonesia, 2024)
This study aims to analyze the implementation of the online Marriage Management Information System (SIMKAH) in marriage administration at the Office of Religious Affairs (KUA) of Bajeng District, Gowa Regency. The main focus of this research is to understand how SIMKAH is implemented and the obstacles faced in the process. This study raises two main questions: (1) What is the role of the KUA in implementing SIMKAH in Bajeng District, Gowa Regency, South Sulawesi? and (2) What are the factors that hinder the implementation of SIMKAH in the KUA? This research uses a qualitative approach with triangulation methods in data collection, which involves observation, interviews, and documentation. The research informants consist of the Head of KUA and administrative staff directly involved in the implementation of SIMKAH. The approach used in this study is normative and juridical, which allows the researcher to understand the legal aspects and regulations related to SIMKAH. The results of the study show that the implementation of SIMKAH at the KUA of Bajeng District has made a positive contribution to improving the efficiency of marriage administration; however, several challenges remain, including limited human resources and inadequate technological infrastructure. These findings are expected to serve as an evaluation for improving technology-based marriage administration services at KUA.